Criminal Liability of the Curator for Illegal Acts in the Independence Principle - Aprita, Serlika; Wulandari, Mona; Qosim, Sarah (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
An entity or individual bankruptcy statement can occur if the debtor fulfills the elements of bankruptcy where the application is submitted to the commercial court by an advocate. The appointment of a curator in one of the contents of a commercial court decision will determine a person or more curators who originate at the request of the bankruptcy applicant, either by the creditor applicant or the debtor applicant himself. This study aims to determine the form and mechanism of the curator's criminal liability to the law based on the principle of independence in managing and settling bankrupt assets. This study uses a prescriptive normative legal research method with a statutory approach. The results of the study state that the recommendation of a curator by the bankruptcy applicant will tend to have a conflict of interest if there is no independent curator in carrying out the obligations mandated to him in Article 15, paragraph (3) of the PKPU UUK. The applicable criminal threat remains based on the source of criminal law in force in Indonesia following the actions of the curator as an individual who is not immune to the law.